Frequency, impact and a preclinical study of novel ERBB gene family mutations in HER2-positive breast cancer - Elster, Naomi (Ther Adv Med Oncol, 2018)
BACKGROUND: Somatic mutations in the ERBB genes (epidermal growth factor receptor: EGFR, ERBB2, ERBB3, ERBB4) promote oncogenesis and lapatinib resistance in metastatic HER2+ (human epidermal growth factor-like receptor 2) breast cancer in vitro. Our study aimed to determine the frequency of mutations in four genes: EGFR, ERBB2, ERBB3 and ERBB4 and to investigate whether these mutations affect cellular behaviour and therapy response in vitro and outcomes after adjuvant trastuzumab-based therapy in clinical samples. METHODS: We performed Agena MassArray analysis of 227 HER2+ breast cancer samples to identify the type and frequency of ERBB family mutations. Of these, two mutations, the somatic mutations ERBB4-V721I and ERBB4-S303F, were stably transfected into HCC1954 (PIK3CA mutant), HCC1569 (PIK3CA wildtype) and BT474 (PIK3CA mutant, ER positive) HER2+ breast cancer cell lines for functional in vitro experiments. RESULTS: A total of 12 somatic, likely deleterious mutations in the kinase and furin-like domains of the ERBB genes (3 EGFR, 1 ERBB2, 3 ERBB3, 5 ERBB4) were identified in 7% of HER2+ breast cancers, with ERBB4 the most frequently mutated gene. The ERBB4-V721I kinase domain mutation significantly increased 3D-colony formation in 3/3 cell lines, whereas ERBB4-S303F did not increase growth rate or 3D colony formation in vitro. ERBB4-V721I sensitized HCC1569 cells (PIK3CA wildtype) to the pan class I PI3K inhibitor copanlisib but increased resistance to the pan-HER family inhibitor afatinib. The combinations of copanlisib with trastuzumab, lapatinib, or afatinib remained synergistic regardless of ERBB4-V721I or ERBB4-S303F mutation status. CONCLUSIONS: ERBB gene family mutations, which are present in 7% of our HER2+ breast cancer cohort, may have the potential to alter cellular behaviour and the efficacy of HER- and PI3K-inhibition.